A new assay for global fibrinolysis capacity (GFC): Investigating a critical system regulating hemostasis and thrombosis and other extravascular functions. Issue 1 (February 2018) - Amiral, Jean; Laroche, Maxime; Seghatchian, Jerard
Abstract: For many years, the importance of fibrinolysis has been recognized, first for its intravascular antithrombotic action, and more recently for its many extravascular activities, associated with matrix degradation and tissue remodeling. In the blood circulation system, fibrinolysis prevents thrombosis, and is associated with various biological and clinical situations: risk factors for cardio-vascular diseases in high risk clinical situations (type II diabetes, hypertension, triglycerides, high BMI, elevated glucose, etc.), probably resulting from a significant reduction of the fibrinolysis potential, and elevation of PAI-1. Noteworthy, t-PA is mainly present as an inactive complex with PAI-1, and its concentration in plasma tends to follow that of PAI-1, but in a lesser extent. Hypofibrinolysis can favor the occurrence of thrombotic events, and possibly other biological dysfunctions. Fibrinolysis activity is however difficult to evaluate as it has a delayed activity after clot formation, is initiated and regulated after fibrin generation, and conversely to clotting, its action is delayed (long lag phase) and slow, before being dramatically amplified leading to rapid clot dissolution. We have designed a new assay for evaluating the global fibrinolytic capacity (GFC) in the body. Reagents are used in association with a specific instrument, which can be connected to any computer, and dedicated software is used for analyzing clot lysis kinetics. The assay is performed in a micro-cuvette, introduced into one of the instrument wells at 37 °C, and light transmittance is continuously measured. Assayed plasma is first supplemented with a limited and constant amount of t-PA with silica and is then clotted with thrombin and calcium. Clot dissolution (measurement of turbidity change) is recorded over time using the dedicated instrument (Lysis Timer), and clot lysis kinetics are analyzed with the associated software: primary and secondary derivatives of the light transmission curve give information on kinetics and completion of clot dissolution. Total assay time is about 1 h (but in the presence of hypofibrinolysis it can be prolonged). The concentration of t-PA used for the assay has been adjusted (100 ng/ml) to obtain an optimal sensitivity to hypofibrinolysis within a short time interval, and clot dissolution occurs within about 45 min for normal individuals, with a broad range from 30 min to 60 min, with some samples presenting a clot dissolution time >60 min (hypofibrinolysis). This new assay is performed with the tested plasma intrinsic factors, especially its own fibrinogen, and only exogeneous t-PA is added. GFC is highly sensitive to PAI-1 activity, but other factors regulating fibrinolysis contribute to the clot dissolution kinetics. Freshly prepared or frozen and thawed citrated plasma can be used. The usefulness of this assay for clinical applications is under investigation. Although fibrinolysis is mainly initiated in the body upon stimulation or blood clotting, and rapidly diluted and inhibited in the circulation, evaluation of its "residual" activity in plasma is expected to reflect its global body potential.